1975
DOI: 10.1530/jrf.0.0450069
|View full text |Cite
|
Sign up to set email alerts
|

TEMPORARY STERILITY PRODUCED IN MALE MICE BY 5-THIO-d-GLUCOSE

Abstract: Summary. When 5-thio-D-glucose was fed to male mice at daily dose levels greater than 30 mg/kg sperm development was completely inhibited within 3 weeks and remained so without impairment of libido for the experimental period of 7 weeks. Removal of this substance from the diet resulted in a resumption of sperm development and fertility within 5 to 8 weeks. Normal litters were sired by males which had recovered after this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Cryptorchidism has been associated with degenerative changes in both Sertoli cells and germ cells [28,29]. Testis energy is provided mostly by glucose, which is the preferred substrate in mammals [30,31], and most germ cell protein s y n t h e s i s i s u n d e r t h e c o n t r o l o f g l u c o s e metabolism [32]. Degenerative changes in the cryptorchid testis m ay be asso ciated with decreased Glut 3 (glucose transporter)-mediated glucose transport in the seminiferous tubules and spermatogonia [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptorchidism has been associated with degenerative changes in both Sertoli cells and germ cells [28,29]. Testis energy is provided mostly by glucose, which is the preferred substrate in mammals [30,31], and most germ cell protein s y n t h e s i s i s u n d e r t h e c o n t r o l o f g l u c o s e metabolism [32]. Degenerative changes in the cryptorchid testis m ay be asso ciated with decreased Glut 3 (glucose transporter)-mediated glucose transport in the seminiferous tubules and spermatogonia [12].…”
Section: Discussionmentioning
confidence: 99%
“…In testes, glucose metabolism is a vital event. Spermatogenesis preservation in vivo relies on glucose metabolism despite the fact that there are low levels of this sugar in tubular liquid (Robinson and Fritz, 1981;Zysk et al, 1975). Metformin helps to restore the body's response to insulin, making it possible to produce the amount of glucose and gastrointestinal absorption needed from the liver.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Zysk et al [22] treatment of mice with thioglucose, 40 or 100 mg/kg body weight per day for three weeks, completely inhibited the development of sperm. The inhibition continued for five to eight weeks after treatment was stopped.…”
Section: Mousementioning
confidence: 96%
“…In 1975 Zysk, Bushway, Whistler, and Carlton [22] reported that spermatogenesis was completely inhibited in male mice treated with the analog of glucose, 5-thio-Dglucose. Not only did the effect appear reversible, but libido was unchanged, and the analog was active when given orally.…”
Section: Introductionmentioning
confidence: 99%